Description of a new member of the family Erysipelotrichaceae: Dakotella fusiforme gen. nov., sp. nov., isolated from healthy human feces - Ghimire, Sudeep; Wongkuna, Supapit; Scaria, Joy (PeerJ, 2020)
A Gram-positive, non-motile, rod-shaped facultative anaerobic bacterial strain SG502T was isolated from healthy human fecal samples in Brookings, SD, USA. The comparison of the 16S rRNA gene placed the strain within the family Erysipelotrichaceae. Within this family, Clostridium innocuum ATCC 14501T, Longicatena caecimuris strain PG-426-CC-2, Eubacterium dolichum DSM 3991T and E. tortuosum DSM 3987T(=ATCC 25548T) were its closest taxa with 95.28%, 94.17%, 93.25%, and 92.75% 16S rRNA sequence identities respectively. The strain SG502T placed itself close to C. innocuum in the 16S rRNA phylogeny. The members of genus Clostridium within family Erysipelotrichaceae was proposed to be reassigned to genus Erysipelatoclostridium to resolve the misclassification of genus Clostridium. Therefore, C. innocuum was also classified into this genus temporarily with the need to reclassify it in the future because of its difference in genomic properties. Similarly, genome sequencing of the strain and comparison with its 16S phylogenetic members and proposed members of the genus Erysipelatoclostridium, SG502T warranted a separate genus even though its 16S rRNA similarity was >95% when comapred to C. innocuum. The strain was 71.8% similar at ANI, 19.8% [17.4–22.2%] at dDDH and 69.65% similar at AAI to its closest neighbor C. innocuum. The genome size was nearly 2,683,792 bp with 32.88 mol% G+C content, which is about half the size of C. innocuum genome and the G+C content revealed 10 mol% difference. Phenotypically, the optimal growth temperature and pH for the strain SG502T were 37 °C and 7.0 respectively. Acetate was the major short-chain fatty acid product of the strain when grown in BHI-M medium. The major cellular fatty acids produced were C18:1ω9c, C18:0and C16:0. Thus, based on the polyphasic analysis, for the type strain SG502T (=DSM 107282T= CCOS 1889T), the name Dakotella fusiforme gen. nov., sp. nov., is proposed.
Keywords: Gut microbiome; New species; Culturomics; Genomic taxonomy; Erysipelotrichaceae; Dakotella fusiforme; New genus